1383 Improvement of Gut Microbiota After Probiotic Treatment of Premature Neonates for the Preventing of Necrotizing Enterocolitis. (October 2012) - Smith, B
Abstract : Purpose: Necrotizing enterocolitis (NEC) is the most common acquired disease of the gastrointestinal tract in premature neonates. Probiotic supplementation with Lactobacillus rhamnosus and Bifidobacterium lactis was introduced to reduce NEC and potentially provide benefits for the preterm neonates. We study if premature neonates were colonized with L. rhamnosus and B. lactis and investigated what influence probiotics had on clinical outcomes. Methods: Faecal samples and clinical information from neonates before and after the introduction of probiotic were collected. 254 premature neonates without probiotics and 101 premature neonates with probiotics all less than 30 weeks of gestation were enrolled. Fecal samples and clinical information during the first month of life from all premature neonates were collected. Results: Clinical information on all premature neonate regarding, gestational age, birth weight, probiotic, antibiotics, food, NEC and dead were collected. A total of 461 feacal samples from premature neonates without probiotics treatment were run, 0.7% were found positive for L. rhamnosus, 0.4% were positive for B. lactis, non of the samples were positive for both. A total of 247 faecal samples from premature neonates treated with probiotics were run, 57.0% of the collected faecal samples contained both L. rhamnosus and B. lactis, 38.0% were positive only for L. rhamnosus, 4.4% were positive for only B. lactis and 0.6% was negative for both probiotics. Conclusion: The probiotic supplementations do reach the gastrointestinal tract and be detected. In general the rate of NEC and death were reduced in premature neonates treated with L. rhamnosus and B. lactis.